Explosive electron emission from a ferroelectric surface initiated in triple junctions; Proceedings of the 23rd International Symposium on Discharges and Electrical Insulation in Vacuum, ISDEIV 2008, Bucharest, september 15-19, 2008; Vol. 1 - Mesyats G. A. Gennady Andreyevich (2008, 2008)
В фонде НТБ ТПУ отсутствует